Osteogenic properties of bioactive sodium titanate/titanium oxide composite coating prepared by anodic oxidation in NaOH electrolyte. (27th April 2021) - Guo, Yuqiang; Wu, Boyao; Hu, Yi; Zuo, Rui; Lu, Xugang; Xiong, Shibing; Huang, Ping; Yang, Bangcheng
Abstract : Our sodium titanate/titanium oxide coating has excellent osteogenic performance and has potential to be used as a bone repair material. Abstract : Titanium oxide and sodium titanate coatings have been proven to have good bioactivity. Here, a composite coating of titanium oxide and sodium titanate was prepared on TC4 titanium alloy substrate with an anodic oxidation method in NaOH solution. The coating is super hydrophilic because of its porous structure with a large number of cracks and a mass of irregular small pit areas. The coating showed bioactivity because it could induce apatite formation in the simulated body fluid, which might be caused by the hydrolysis of the sodium titanate in the biological environment. Cell culture experiments with rabbit bone marrow MSCs showed the composite coating had no cytotoxicity, and it could promote the proliferation and differentiation of MSCs. Animal experiments showed that the composite coating had good osteogenic function after it was implanted in a rabbit femur. The results indicated that it has potential as a new type of bioactive Ti surface by the anodic oxidation method in NaOH solution.